Excess risk of fatal road traffic accidents on the day of daylight saving time change - Prats-Uribe, A; Tobías, A; Prieto-Alhambra, D (Lippincott, Williams & Wilkins, 2018)
Daylight Saving Time (DST) is the practice of setting the clocks forward 1 hour from standard time during the summer months, and back again in the fall, in order to make better use of natural daylight. It is applied in a large number of countries worldwide affecting 1.5 billion people. Changes in light hours and sleep disruption occurring during DST changes, have been theorised to increase risk of traffic injuries. However, a recent review found inconclusive results on whether DST increased or decreased the risk of road traffic collision, especially in the short-term. We estimated the risk of daily fatal traffic accidents following summer and fall DST changes in Spain.